"Thunder Stone" from Baba lokva Site (Archaeologia Adriatica, 2017)
The author analyzes the prehistoric stone axe-hammer found at the Baba lokva medieval settlement site in Kaštela (14th to 17th centuries), observing it from the aspect of mythological perception of such finds as apotropaic objects (amulets, talismans). Drawing numerous ethnological parallels in Croatia, Bosnia and other parts of Central Europe and archaeological parallels in northern Croatia (Ludbreg – Iovia, Paka fortification) and Dalmatia (Begovača – Biljane Donje), the author argues that the Baba lokva axe was used to protect dwellings from lightning or, perhaps, as a personal protection of its owner who carried it. It is a custom that has been preserved since the prehistoric pagan (proto-Slavic and proto-Indo-European) times, surviving to this day as part of traditional culture.
Keywords: "thunder stone"; Baba lokva; amulet; talisman